Endogenous Information and Simplifying Insurance Choice - Brown, Zach Y.; Jeon, Jihye (Econometrica, 2024)
In markets with complicated products, individuals may choose how much time and effort to spend understanding and comparing alternatives. Focusing on insurance choice, we find evidence consistent with individuals acquiring more information when there are larger consequences from making an uninformed choice. Building on the rational inattention literature, we develop and estimate a parsimonious demand model in which individuals choose how much to research difficult‐to‐observe characteristics. We use our estimates to evaluate policies that simplify choice. Reducing the number of plans can raise welfare through improved choice as well as savings in information costs. Capping out‐of‐pocket costs generates larger welfare gains than standard models. The empirical model can be applied to other settings to examine the regulation of complex products.